Observed Performance and FEM-Based Parametric Analysis of a Top-Down Deep Excavation in Soil-Rock Composite Stratum - Gang Lei; Panpan Guo; Fucai Hua; Xiaonan Gong; Lina Luo (Geofluids)
This paper investigates the performance of a top-down deep excavation in soil-rock composite stratum. The behavior of the excavation bracing system, consisting of ground anchors and end-suspended piles, has not been well understood due to the lack of relevant research. Based on the observed data of a typical deep excavation case history for the May Fourth Square Station in Tsingtao, China, the characteristics of the horizontal and vertical pile displacements, ground surface settlements, building settlements, axial forces in ground anchors, earth pressure, and pore water pressure during excavation were analysed. Two-dimensional finite element simulations were carried out to further explore the deformation and internal force responses of end-suspended piles and to capture the effects of pile diameter, embedded depth, and rock-socketed depth on the horizontal displacement and bending moment distributions along the pile shaft. It was found that the pattern of the vertical pile displacements could be categorized into three types: rapid settlement, slow settlement, and rapid heave. The magnitudes of the ground and building responses can be well controlled within allowable limits by combining the top-down method with the adopted bracing system. Among the investigated parameters, pile diameter is dominant in affecting the horizontal pile displacement. The primary influence zone for pile bending moment varies, depending on the parameters. It is recommended that a combination of top-down method, ground anchors, and end-suspended piles be adopted for restraining excavation deformation and lowering construction costs of similar deep excavations in soil-rock composite stratum.